Cardiac involvement as the main presenting feature in eosinophilic granulomatosis with polyangiitis. (12th July 2013) - McAleavey, Neil; Millar, Auleen; Pendleton, Adrian
Abstract : Eosinophilic granulomatosis with polyangiitis is usually characterised by asthma, allergic rhinitis and peripheral eosinophilia. Presentations can vary greatly especially when there is cardiac involvement as demonstrated in these two case reports. Patient A initially presented to casualty with severe sinus pain and was diagnosed with severe sinonasal polyposis. After routine nasal polypectomy he had a cardiac arrest and was transferred to intensive care. Patient B presented to his general practitioner with a 4-week history of breathlessness, joint pain and a rash resulting in admission to hospital. Both patients had significant eosinophilia on routine bloods. High-sensitivity troponin T levels were raised in both; however, patient B's was significantly higher. Patient A had a large pericardial effusion on echo, the aspirate of which revealed numerous eosinophils. Patient B's echo was normal. Patient A's cardiac MRI was normal while Patient B's revealed myocarditis. Both were successfully treated with intravenous methylprednisolone and cyclophosphamide.